Gestalt theory and the guidance of the gaze in early Buddhist stupa reliefs - Voegtle Simone (Gestalt Theory)
Buddhist stupa reliefs, with their specific placement in architectural space, create unique conditions for their viewing. They were attached to religious monuments (stupas) and were looked at during the ritual of circumambulation. This article examines how various strategies of image composition were used to optimize the readability of narrative images and enable the perception of a chronological flow. As a close examination of the pictorial structure shows, the strategies set out in Gestalt theory are also applied in images that were viewed under circumstances contrary to Western habits. The examples discussed, showing scenes from the life of the Buddha, were subject to different conditions of viewing and a different art-historical background but followed the same perceptual-psychological imprint.